"I am a young immigrant woman doing physics and on top of that I am Muslim": Identities, intersections, and negotiations. Issue 3 (20th August 2019) - Avraamidou, Lucy
Abstract: Framed within intersectionality and using science identity as a unit of analysis, in this single case study I explore the barriers, difficulties, and conflicts that Amina, a young Muslim woman, immigrant in Western Europe confronted throughout her trajectory in physics and the ways in which her multiple identities intersected. The main sources of data consisted of three long biographical interviews, which were analyzed through a constant comparative method. The analysis of the data provided insights into how intrapersonal, interpersonal, sociocultural factors, alongside a myriad of experiences nurtured Amina's intersectional identities and what this may mean for Muslim women's participation in physics. The findings are summarized in two main assertions: (a) Amina was confronted with various barriers across her journey in physics with the intersection of religion and gender being the major barrier to her perceived recognition due to cultural expectations, sociopolitical factors, and negative stereotypes and (b) Amina's social class, religion, gender performance, and ethnic status positioned her as Other in various places throughout her trajectory in physics, and consequently hindered her sense of belonging. These findings suggest the urgency and importance of: (a) examining the intersection of science identity with other identities, especially, religion, gender, and ethnicity for the purpose of extrapolating a more comprehensive understanding of how minoritized groups participate in science; (b) rethinking recognition through an explicit intersectionality lens across various geographical and sociopolitical contexts; and (c) transforming physics into a diverse world where multiple ways of being are recognized, where minoritized groups will not have to compartmentalize parts of their identities to exist, and where they can perform their authentic and intersectional identities.